The spatial regulation of Auxin Response Factors - Jingyi, Han (2021)
Auxin regulates plant growth and development through the transcription factors (TFs) of the AUXIN RESPONSE FACTOR (ARF) gene family. Class A ARFs, ARF5, 6, 7, 8 and 19 are transcriptional activators, and control many developmental processes. However, we only have limited understanding on how these ARFs can mediate such diverse developmental responses. In this study we investigated expression patterns of ARFs in the root and shoot apical meristems and showed that they have specific domains of expression. Through a yeast one-hybrid and protoplast assay, we identified a network of transcriptional repressors which regulated these ARFs. To validate this network, we over-expressed candidate TFs in ARF reporter lines, generated new reporter lines to check the co-expression of TFs and ARFs in specific tissues and carefully quantified auxin specific phenotypes in the mutants of candidate TFs. Collectively, these results support a mechanism in which the spatial and temporal expression of ARFs is modulated mainly by tissue specific repression.